Millennial-scale East Asian monsoon variability of the last glacial deduced from annually laminated sediments from Lake Sihailongwan, N.E. China. (1st December 2018) - Mingram, Jens; Stebich, Martina; Schettler, Georg; Hu, Yaqin; Rioual, Patrick; Nowaczyk, Norbert; Dulski, Peter; You, Haitao; Opitz, Stephan; Liu, Qiang; Liu, Jiaqi
Abstract: Lake Sihailongwan in Jilin province, NE China, provides the first continuous and almost entirely seasonally laminated sediment record on the East Asian mainland comprising the complete Holocene, the Late-glacial period, and large parts of the Last Glacial. Sediment and palynological proxy data provide a finely resolved regional environmental history of the East Asian monsoon. A varve-based chronology (shl-vc2) has been established for the last 65, 000 years and allows a detailed comparison with other long regional and global palaeoclimate records. Vegetation density of the study area depends, on the long run, on precessionally forced insolation changes, with superimposed millennial-scale variability during the Last Glacial. Periodic increase of organic carbon content and thermophilous tree species like Ulmus and Fraxinus and contemporary decrease of shrub Alnus precisely mirror millennial-scale climatic variations primarily known from Greenland ice-cores as Dansgaard-Oeschger cycles, as well as Late-glacial period climate changes. Percentages of trees & shrubs pollen and in particular lake productivity-related data reveal substantial differences between interstadial intensities, with those between 50 and 60 ka BP being more pronounced than the following ones. Highlights: A varved lake sediment record covers the last 65 ka of East Asian monsoon history. Influence of local environmental thresholds and climate change on proxy data. Strong similarities between East Asian monsoon and Dansgaard-Oeschger cycles. Week East Asian Monsoon during Heinrich events.